PEDAGOGICAL SUPPORT AS A MEANS REGULATION OF GENERAL EDUCATIONAL ENVIRONMENTS IN MODERN SCHOOL PRACTICE (Pedagogy of Higher and Secondary Education, 2004)
The article is an orientation on a modern adjustment of general education surrounds in the practice of contemporary school.